THE IMPACT OF SERVQUAL DIMENSIONS ON CUSTOMER LOYALTY - Septi Yawan, Andika; Prakosa, Adhi; Imam Basri, Anindita; Sudaryana, Arif; Farhan, Fikri (CV. Fahr Publishing, 2023)
The need for an internet network is important. This study aims to predict the impact of SERVQUAL dimensions of internet service providers on customer loyalty in Indonesia. This research is quantitative research with SEM-PLS analysis. Data collection by questionnaire, with a sample of 115 internet service provider (ISP) customers in Yogyakarta. The test results with the structural model are responsiveness and empathy do not affect customer loyalty.